A capacity maximization scheme for intersection management with automated vehicles. (September 2018) - Sun, Weili; Zheng, Jianfeng; Liu, Henry X.
Highlights: MCross is a new intersection operation scheme for connected and automated vehicles. This new scheme maximizes intersection capacity by utilizing all lanes of a road simultaneously. Numerical examples show that MCross can almost double the intersection capacity. Abstract: With the advent of connected and automated vehicle technology, in this paper, we propose an innovative intersection operation scheme named as MCross: M aximum C apacity inteR section O peration S cheme with S ignals. This new scheme maximizes intersection capacity by utilizing all lanes of a road simultaneously. Lane assignment and green durations are dynamically optimized by solving a multi-objective mixed-integer non-linear programming problem. The demand conditions under which full capacity can be achieved in MCross are derived analytically. Numerical examples show that MCross can almost double the intersection capacity (increase by as high as 99.51% in comparison to that in conventional signal operation scheme).